Thoracic Radionecrosis Following Repeated Cardiac Catheterization - Borut Banic; Bernhard Meier; Andrej Banic; Christian Weinand (Radiology Research and Practice)
Radiodermatitis is a known complication in patients having undergone radiotherapy. It usually appears 2 to 5 years after irradiation. We are reporting on a case of radiodermatitis that occurred within months after coronary dilatation and stenting. It started with painful swelling, followed by a typical appearance on the skin surface. Histological finding confirmed the diagnosis. However, magnetic resonance imaging showed changes in the subcutaneous tissue extending into the ribs. A radical debridement was performed including removal of a partially necrotic 4th rib. The defect was closed with a latissimus dorsi transposition flap. Our findings are compared with the literature reports.